2018
DOI: 10.1136/bcr-2018-224722
|View full text |Cite
|
Sign up to set email alerts
|

Severe bone marrow suppression due to methotrexate toxicity following aceclofenac-induced acute kidney injury

Abstract: Methotrexate is one of the most commonly used drugs in autoimmune disorders like rheumatoid arthritis. Gastrointestinal symptoms like nausea and stomatitis, skin rashes, alopecia, central nervous system symptoms like headache and confusion, hepatotoxicity and myelosuppression are some of the adverse effects. However, low oral doses on a weekly basis seldom show any signs of toxicity. Leucovorin or folinic acid is given along with methotrexate as rescue to reduce the toxic effects like bone marrow suppression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Amid worsening pancytopenia, a bone marrow biopsy was warranted due to multiple potential contributors. The results were concordant with previously reported findings of bone marrow biopsies found with MTX toxicity in the literature: hypocellular marrow with trilineage hypoplasia consistent with myelosuppression induced by MTX [ 10 ]. There were also reported neutrophils hypersegmentation and erythrocyte budding, a finding that is also found in B12 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…Amid worsening pancytopenia, a bone marrow biopsy was warranted due to multiple potential contributors. The results were concordant with previously reported findings of bone marrow biopsies found with MTX toxicity in the literature: hypocellular marrow with trilineage hypoplasia consistent with myelosuppression induced by MTX [ 10 ]. There were also reported neutrophils hypersegmentation and erythrocyte budding, a finding that is also found in B12 deficiency.…”
Section: Discussionsupporting
confidence: 92%
“…In renal impairment cases, low doses are enough to cause bone marrow suppression and also diabetes mellitus may have role for altering the pharmacokinetics of MTX by physiological environment altering of the body [9]. In the year 1996, a literature review by Pearce and Wilson have identified 47 cases of MTX induced skin ulceration which was reported between the years of 1951 and 1967 and further of 17 cases between the year 1967 and 1996 (including two of their own patients and those of which by Roenigk et al and Lawrence and Dhal) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Риск желудочно-кишечных кровотечений или изъязвлений может повышаться при использовании НПВП одновременно с системными глюкокортикостероидами, антикоагулянтами (например, варфарином), селективными ингибиторами обратного захвата серотонина или антиагрегантами, например, аспирином. Совместное применение НПВП и метотрексата может повысить уровень метотрексата в плазме, что приводит к увеличению его токсичности [35,53,56].…”
Section: использование ацеклофенака у пожилых пациентовunclassified